PENGARUH KUALITAS PELAYANAN, HUBUNGAN PELANGGAN DAN CITRA PERUSAHAAN TERHADAP LOYALITAS MELALUI KEPUASAN NASABAH - Basuki Sri Rahayu; Endang Saryanti (ADVANCE, 2014)
This study aims is to determine the Effects ofService Quality, Customer Relations and Corporate Image Of Loyalty Through Customer Satisfaction In PD. BPR BKK Boyolali.This study is a survey research. The data used primary data collected through questionnaires to customers PD. BPR BKK Boyolali. The data obtained were tested using the test validity, reliability, linearity test, path analysis, t test, F test, test R2in total.The results of the t test, the first equation shows that the variables of service quality and corporate image/company image respectively positive and significant impact, while customer relationship/effect relationship is positive but not significant. While the second equation only service quality are significant effect on customer loyalty, indicating that due to the location of existing districts in the region, in general, customer-oriented transactions with a sense of security and fast employee service in the transaction of PD. BPR BKK Boyolali. Keywords : Quality of Service , Customer Relations , Corporate Image , job satisfaction,Loyalty.